Exponential and Logarithmic Functions - Tamara Todorova (Tamara Todorova, Problems Book to Accompany Mathematics for Economists, 2010)
Exponential functions find applications in economics in relation to growth and economic dynamics. In these fields, quite often the choice variable is time and economists are trying to determine the best timing for certain economic activities to take place. An exponential function is one in which the independent variable appears in the exponent. Very often that exponent is time.
Additional information: In highly mathematical courses, it is a truism that students learn by doing, not by reading. Tamara Todorova's Problems Book to Accompany Mathematics for Economists provides a life line for students seeking an extra leg up in challenging courses. Beginning with college-level mathematics, this comprehensive workbook presents an extensive number of economics focused problem sets, with clear and detailed solutions for each one. By keeping the focus on economic applications, Todorova provides economics students with the mathematical tools they need for academic success. For years, Professor Todorova has taught microeconomic courses to economists and non-economists, introduced students to new institutional economics as a modern trend in economics, and taught quantitative methods and their application to economic theory, marketing, and advertising.
Keywords: 330; Exponential functions; Logarithmic functions